Synthesis and 13C NMR spectroscopy of 13C-labeled α,ω-diphenylpolyynes - Tykwinski, Rik; Thanh Luu (Synthesis-Stuttgart, 2012)
The synthesis of three C-labeled α,ω- diphenylpolyynes is described. The known positions of the labeled carbon atoms allow assignment of the resonances in the C NMR spectra and identification of trends in the chemical shifts. © Georg Thieme Verlag Stuttgart · New York.